2017
DOI: 10.1007/jhep03(2017)041
|View full text |Cite
|
Sign up to set email alerts
|

Hyperscaling-violating Lifshitz hydrodynamics from black-holes: part II

Abstract: The derivation of Lifshitz-invariant hydrodynamics from holography, presented in [1] is generalized to arbitrary hyperscaling violating Lifshitz scaling theories with an unbroken U(1) symmetry. The hydrodynamics emerging is non-relativistic with scalar "forcing". By a redefinition of the pressure it becomes standard non-relativistic hydrodynamics in the presence of specific chemical potential for the mass current. The hydrodynamics is compatible with the scaling theory of Lifshitz invariance with hyperscaling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…Of course, one will immediately ask whether there is a way to consistently truncate the series and, if the truncation to first derivative is problematic, how many orders in the derivative expansion we should keep. It would be interesting to use the gauge/gravity duality, particularly the method to extract nonlinear constitutive relations from a gravity dual such as [25,[38][39][40][41][42][43], to gain more insight into these questions. (iii) The entropy current: Recently it was shown that there is a way of making first order uncharged Lorentzian hydrodynamics stable, evading the shortcoming of the constructions mentioned above [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, one will immediately ask whether there is a way to consistently truncate the series and, if the truncation to first derivative is problematic, how many orders in the derivative expansion we should keep. It would be interesting to use the gauge/gravity duality, particularly the method to extract nonlinear constitutive relations from a gravity dual such as [25,[38][39][40][41][42][43], to gain more insight into these questions. (iii) The entropy current: Recently it was shown that there is a way of making first order uncharged Lorentzian hydrodynamics stable, evading the shortcoming of the constructions mentioned above [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous investigations appear in e.g. [15][16][17][18][19][20][21][22][23][24][25][26][27], in part reviewed in [5]. In the context of gauge/gravity duality [1][2][3][4] for relativistic theories, various transport properties are encoded in the quasinormal modes of the dual gravitational black branes, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…4 Hydrodynamics for z = 2 Schrödinger systems was considered from a modern perspective in e.g. Refs [10,11,12,13,14,15,16,17,18]…”
mentioning
confidence: 99%